The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/14992027.2013.783719
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and frequency ofGJB2mutations in a cohort of 264 Portuguese nonsyndromic sensorineural hearing loss patients

Abstract: This study provides clear demonstration that mutations in the GJB2 gene are an important cause of NSSHL in Portugal, thus representing a valuable indicator as regards therapeutical and rehabilitation options, as well as genetic counseling of these patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…GJB2 encodes gap junction protein connexin 26 (Cx26), which has been implicated in the maintenance of K + homeostasis in the inner ear [4]. also the most common GJB2 mutation causing NSHL in Portugal, with a prevalence of 15.9% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GJB2 encodes gap junction protein connexin 26 (Cx26), which has been implicated in the maintenance of K + homeostasis in the inner ear [4]. also the most common GJB2 mutation causing NSHL in Portugal, with a prevalence of 15.9% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another variation in the GJB2 gene that has been found with a high prevalence in studies in NSHL populations, including Portugal, c.101 T ! C (Met34Thr), a methionine-to-threonine substitution at amino acid 34 [2,6,10]. This variant was found at a lower frequency in NSHL patients, compared to the 35delG mutation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen additional variant alleles were detected by SNPscan. In terms of the positive rate comparison, although the pathogenicity of the variant c.109G N A in the GJB2 gene remains questionable, most recent studies suggest that this site change is a pathological mutation [16,17]. Hence, the positive rate of the SNPscan kit is 51.2%, which is higher than the 44.4% of the 15 loci SNaPshot analysis system.…”
Section: Discussionmentioning
confidence: 88%
“…About 28 kinds of variants were pathological mutations, which have been determined previously. The category of one nucleotide change was unknown (c.109G N A in the GJB2 gene), although most recent studies suggested that this site change is a pathological mutation [16,17]. The most prevalent mutation in these subjects was c.235delC in the GJB2 gene, and this mutation accounts for 40.0% (76/190) of all mutant alleles.…”
Section: Resultsmentioning
confidence: 95%
“…Pollak et al (2007) [24] studied carriers of the p.Met34Thr/ c.35delG compound heterozygosity and also concluded that the p.Met34Thr variant presents a pathogenic role, with low penetrance and late onset and progressive HL. In our previous work (Matos et al, 2013) [25], we have observed the p.Met34Thr variant in 1,3% of the GJB2 alleles among 264 Portuguese nonsyndromic sensorineural HL patients. Two of these patients presented the p.Met34Thr/c.35delG and p.Met34Thr/p.Val95Met compound genotypes, respectively.…”
Section: Discussionmentioning
confidence: 98%